Corporate Social Responsibility and the Chief Executive Officer: determinants of a positive strategic intention towards Corporate Social Responsibility. (4th December 2008) - Peters, Richard; Koufteros, Xenophon; Berman, Shawn
Corporate Social Responsibility (CSR) has evolved from mere social philanthropy to its present conceptualisation as a distinct organisational strategy. This study treats CSR as a strategic decision, and focuses on the sense-making process of the Chief Executive Officer (CEO) with respect to pro-CSR intent. We consider collectively multiple structural determinants including personal values, stakeholder culture and environmental munificence and relate them to an intention by the CEO to act in a socially responsible manner.